2009
DOI: 10.1248/jhs.55.495
|View full text |Cite
|
Sign up to set email alerts
|

Direct Analysis of Conjugate Metabolites of Methamphetamine, 3,4-Methylenedioxymethamphetamine, and Their Designer Drugs in Biological Fluids

Abstract: This review summarizes technical improvements in the forensic analysis for conjugate metabolites of methamphetamine (MA), 3,4-methylenedioxymethamphetamine (MDMA) and their designer drugs. The improvements include the establishments of liquid chromatography-mass spectrometry-mass spectrometry (LC-MS-MS) in combination with the pretreatment methods. The direct determination techniques for the conjugates proved to be effective in rapidly and accurately examining many biological specimens without annoying hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…Here we showed methamphetamine and its metabolites interact with hOCT1-3 and hMATE1/2-K at clinically relevant concentrations (Melega et al, 2007;Shima et al, 2009). We further demonstrated that methamphetamine and amphetamine are substrates of hOCT2, hMATE1, and hMATE2-K, but not hOCT1or hOCT3.…”
Section: Discussionsupporting
confidence: 57%
“…Here we showed methamphetamine and its metabolites interact with hOCT1-3 and hMATE1/2-K at clinically relevant concentrations (Melega et al, 2007;Shima et al, 2009). We further demonstrated that methamphetamine and amphetamine are substrates of hOCT2, hMATE1, and hMATE2-K, but not hOCT1or hOCT3.…”
Section: Discussionsupporting
confidence: 57%
“…Many reviews have focused on the drugs of abuse themselves, [5][6][7][8] specific biological specimens, such as hair, 9,10) the methodology, 11,12) or the analytical instruments. [2][3][4] In this review, on the basis of reports published in the last three years (2008-2010) describing the analyses of drugs of abuse in biological specimens, different perspectives, such as the need for and the background of drug analysis in biological specimens, and difficulty of drug testing in biological specimens, are introduced together with some actual examples.…”
Section: Introductionmentioning
confidence: 99%
“…27 In accordance, Phase II glucuronide products of methamphetamine metabolism were targeted by the comprehensive methamphetamine metabolism analysis method employed in the present study. In contrast to human specimen data reported in previous work, direct LC-MS analysis in the present study was unable to detect methamphetamine metabolite glucuronide formation in any in vitro system examined, despite the presence of active Phase I oxidation and Phase II glucuronidation mechanisms.…”
Section: Methamphetamine Metabolism Discussionmentioning
confidence: 99%
“…27 While minor differences in quantities of hydroxylated metabolites were noted between assays containing the cofactors necessary to form glucuronide conjugates (+1/2) and those lacking UDP-GlcUA (+1), the analysis method did not directly detect the presence of glucuronic acid conjugated metabolites. …”
Section: Secondary Metabolitesmentioning
confidence: 93%
See 1 more Smart Citation